Taking Anamnesis and Examination of the Articulatory Apparatus with Erased Dysarthria - S. J, Achilova (Research Parks Publishing LLC, 2022)
This article examines the articulatory speech apparatus in children with dysarthria and the collection of anamnestic data. Information on their analysis is also provided.